PREPARING OF SACCHAROMYCES CEREVICIAE SYNBIOTIC FOR REDUCING EXPERMENTAL INFECTION OF SALMONELLA TYPHIMURIUM IN BROILER 1 –EARLY AGE ( 1 –15 DAYS ): Faris A. Al-Obaidi , Ghada A. Qatan and Shahrazad M. Al-Shadeedi - Al-Obaidi, Faris A. (The Iraqi Journal of Veterinary Medicine, 2008)
This study was conducted at the College of Veterinary Medicine ,University of Baghdad to prepare synbiotic of Sacch. cerevisiae and used as 0.1 and 0 .2 % of feed (T2,T3) for reducing the experimental infection of Salmonella typhimurium to broiler chicks ( 1-15 days) by using 40 birds divided into four treatments , T1 was negative control with 0.1 % synbiotics and T4 was positive control with experimental infection only , production and blood parameters were studed , and the results showed the following: A synbiotic of Sacch. cerevisiae was prepared at the first time locally which have 10 7 cfu of Sacch. cerevisiae and 10 mg Mannan Oligosaccharide per gram . Using 0.1 and 0.2 % of Sacch. cerevisiae synbiotic improved production parameters and reduced experimental infection via increase body weight and feed conversion and decrease mortality and physiological stress of experimental infection by rebalance of some studied blood parameters which inclued PCV , RBCs , WBCs and Hb.